2021
DOI: 10.1089/pop.2019.0165
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Associated with Sleep Quality and Duration Among Older Adults with Chronic Pain

Abstract: Sleep complaints are common among older adults with chronic pain. Because of the risk of significant side effects, sleep medications are not recommended as first-line treatments. Little is known about the association between positive psychosocial factors and sleep, but further awareness could support non-drug strategies to minimize poor sleep. The purpose of this study was to (1) determine the prevalence of self-reported poor sleep quality and short/long sleep duration in a population of older adults with chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
1
28
0
4
Order By: Relevance
“…Results are from proportional odds models. Results are displayed as ORs of change in sleep duration (taking 7-9 hours as reference) per unit increase in the original scale of generalized trust, visits and interaction with friends, participation of organized social activities, emotional social support, or instrumental social support a Adjusted for gender, age, education, marital status, current residential area, household annual income, living alone, and pension status b Adjusted for gender, age, education, marital status, current residential area, household annual income, living alone, pension status, smoking, alcohol drinking, and physical activity c Adjusted for gender, age, education, marital status, current residential area, household annual income, living alone, pension status, smoking, alcohol drinking, physical activity, sleep quality, BMI, depression, ADL, cognitive function, NCD, and comorbidity *p < 0.05; **p < 0.01; ***p < 0.001 in rural areas would suffer more from depression [63], which was found associated with higher risk of longer sleep duration and daytime napping in previous research [64,65]. Differences in family responsibilities have led to significant gender differences in sleep outcomes, such as longer self-reported sleep in women [66].Women in Chinese society, especially in rural areas, always spend more time to give family support such as unpaid care responsibilities for grand-children and spouse [67], which makes their social capital more concentrated on their family and relatives [68].…”
Section: Table 2 Logistic Regression Analysis Of the Association Betw...mentioning
confidence: 77%
“…Results are from proportional odds models. Results are displayed as ORs of change in sleep duration (taking 7-9 hours as reference) per unit increase in the original scale of generalized trust, visits and interaction with friends, participation of organized social activities, emotional social support, or instrumental social support a Adjusted for gender, age, education, marital status, current residential area, household annual income, living alone, and pension status b Adjusted for gender, age, education, marital status, current residential area, household annual income, living alone, pension status, smoking, alcohol drinking, and physical activity c Adjusted for gender, age, education, marital status, current residential area, household annual income, living alone, pension status, smoking, alcohol drinking, physical activity, sleep quality, BMI, depression, ADL, cognitive function, NCD, and comorbidity *p < 0.05; **p < 0.01; ***p < 0.001 in rural areas would suffer more from depression [63], which was found associated with higher risk of longer sleep duration and daytime napping in previous research [64,65]. Differences in family responsibilities have led to significant gender differences in sleep outcomes, such as longer self-reported sleep in women [66].Women in Chinese society, especially in rural areas, always spend more time to give family support such as unpaid care responsibilities for grand-children and spouse [67], which makes their social capital more concentrated on their family and relatives [68].…”
Section: Table 2 Logistic Regression Analysis Of the Association Betw...mentioning
confidence: 77%
“…32 In another study, Zaidel et al determined the ICIQ-SF scores of the individuals in the pre-interview as 14.60 ± 4.3. 33 In the study Arias et al, it was found that the incidence of incontinence over the age of 70 was 30%. 34 These findings are similar to the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…Inadequate sleep creates a vicious circle after a certain period of time, leading to increased sensitivity to pain, disgust and distractibility. 30 In the literature, hypertension and diabetes are the leading risk factors for coronary artery disease. 31 In this present study, patients with HT and on antihypertensives were found to have more fatigue.…”
Section: Discussionmentioning
confidence: 99%